2004
DOI: 10.1007/s10211-004-0102-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment in a live-bearing fish (Poecilia mexicana): influence of population-specific male mating behaviour

Abstract: We investigated male sexual behaviour and the cost of sexual harassment, as measured by the reduction of female feeding time in the presence of a male, in a cavedwelling population of Poecilia mexicana, in which sexual harassment does not occur naturally. We asked whether the lack of sexual harassment in this population is due to low sexual activity of the males, or low feeding motivation of the females. We experimentally increased the sexual activity of males or the females' feeding motivation, or we used a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…A recent study has shown that even cave molly males with increased sexual motivation (after being isolated from females for 7-10 days) do not show the size-dependent pattern of sexual behaviour that is known in surface-dwelling males, although they strongly increase their sexual activity (Plath et al 2004b). This further supports the idea that sizedependent mating behaviour is genetically fixed in the cave molly.…”
Section: Discussionmentioning
confidence: 71%
“…A recent study has shown that even cave molly males with increased sexual motivation (after being isolated from females for 7-10 days) do not show the size-dependent pattern of sexual behaviour that is known in surface-dwelling males, although they strongly increase their sexual activity (Plath et al 2004b). This further supports the idea that sizedependent mating behaviour is genetically fixed in the cave molly.…”
Section: Discussionmentioning
confidence: 71%
“…At least in the case of nipping behaviour, male body size and the number of sexual behaviours were negatively correlated in this experiment. Such conditional use of size-dependent male mating behaviour was not found in the cave molly, where the genetic basis of this pattern is probably lost (Plath et al 2004b). Apparently, the El Azufre population has an intermediate status between the cave and the nearest clear-water (Río Oxolotan) population.…”
Section: Discussionmentioning
confidence: 80%
“…We examined whether cave mollies show size-dependent mating behaviour when they increase their sexual activity after sexual deprivation (Plath et al 2004b). However, no correlation between male size and the frequency of male sexual behaviours was found even when cave molly males showed increased sexual behaviour after sexual deprivation (Plath et al 2004b). The genetic basis for typical size-dependent male mating behaviour is probably lacking in the cave population.…”
Section: Size-dependent Male Mating Behaviour In Molliesmentioning
confidence: 99%
See 2 more Smart Citations